The Strategic Role of E-Payment in Linking Sharia Financial Literacy, Financial Behavior, and MSME Welfare in Sulawesi Barat - Hidayat, Rahmat (Indonesian Journal Publisher, 2025)
This study examines the role of e-payment usage in mediating the relationship between Sharia financial literacy and financial behavior on the financial well-being of Micro, Small, and Medium Enterprises (MSMEs) in West Sulawesi, Indonesia. Using a quantitative causal research design, data were collected from 115 MSME owners and managers engaged in trade, culinary, and service sectors through a structured questionnaire employing a five-point Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Sharia financial literacy and financial behavior have a significant positive effect on e-payment usage, with financial behavior exerting a stronger influence. However, neither Sharia financial literacy nor financial behavior directly affects MSME financial well-being. Conversely, e-payment usage has a strong and significant positive effect on financial well-being and fully mediates the relationship between Sharia financial literacy and financial behavior with financial well-being. These results underscore the strategic role of Sharia-compliant e-payment adoption in enhancing MSME welfare by improving transaction efficiency, expanding market reach, and reducing operational costs. The study contributes to the literature by integrating Sharia financial literacy, financial behavior, and e-payment into a mediation model within the specific context of MSMEs in West Sulawesi. Practical implications are offered for policymakers, financial institutions, and MSME practitioners to strengthen Sharia financial literacy and encourage e-payment adoption as a pathway to sustainable economic growth.